2011
DOI: 10.1523/jneurosci.6421-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Human Dorsal Striatal Activity during Choice Discriminates Reinforcement Learning Behavior from the Gambler's Fallacy

Abstract: Reinforcement learning theory has generated substantial interest in neurobiology, particularly because of the resemblance between phasic dopamine and reward prediction errors. Actor-critic theories have been adapted to account for the functions of the striatum, with parts of the dorsal striatum equated to the actor. Here, we specifically test whether the human dorsal striatum-as predicted by an actor-critic instantiation-is used on a trial-to-trial basis at the time of choice to choose in accordance with reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 52 publications
5
28
0
1
Order By: Relevance
“…Coordinates for the VS were taken from meta-analytic data of previous functional magnetic resonance imaging (fMRI) studies of MID task performance (left: (Knutson and Greer, 2008), consistent with other recent studies using this version of the MID (eg, Balodis et al, 2012). The DS was defined using coordinates from published fMRI data indicating activation of the DS in response to a range of different rewarding stimuli (left: x ¼ À 9, y ¼ 3, z ¼ 15; right: x ¼ 9, y ¼ 3, z ¼ 15) (Valentin and O'Doherty, 2009), consistent with other fMRI studies focusing on the DS (eg, Jessup and O'Doherty, 2011).…”
Section: Region-of-interest (Roi) Analysessupporting
confidence: 69%
“…Coordinates for the VS were taken from meta-analytic data of previous functional magnetic resonance imaging (fMRI) studies of MID task performance (left: (Knutson and Greer, 2008), consistent with other recent studies using this version of the MID (eg, Balodis et al, 2012). The DS was defined using coordinates from published fMRI data indicating activation of the DS in response to a range of different rewarding stimuli (left: x ¼ À 9, y ¼ 3, z ¼ 15; right: x ¼ 9, y ¼ 3, z ¼ 15) (Valentin and O'Doherty, 2009), consistent with other fMRI studies focusing on the DS (eg, Jessup and O'Doherty, 2011).…”
Section: Region-of-interest (Roi) Analysessupporting
confidence: 69%
“…3; Supplemental material). These data confirm that the dorsal striatum participates in reward processing, and confirm its sensitivity to RPE signals (Amiez et al, 2012;Apicella et al, 2009Apicella et al, , 2011Brovelli et al, 2008;Haruno and Kawato, 2006b;Jessup and O'Doherty, 2011;Lau and Glimcher, 2007;Yamada et al, 2011;Zink et al, 2004). Interestingly, using a variant of the problem-solving task, Yamada et al reported that different populations of striatal cells code for positive feedback, for error feedback, for probability, and for search-repeat effect (Yamada et al, 2011).…”
Section: Modulation Of Feedback-related Activity By Uncertainty Durinmentioning
confidence: 54%
“…Anterior insula appears to represent risk predictions during choice, and risk prediction errors in response to decision outcomes (50). Such predictions about the uncertainty of the environment are relevant to the near-miss effect (51) and gambler's fallacy (35), and arguably less relevant to the illusion of control effect that did not vary across lesion groups here. Past work in cases with insula lesions has shown increases in risktaking and impaired discrimination between risky gains and risky losses (31,52).…”
Section: Discussionmentioning
confidence: 79%
“…This apparent inversion implies some systematic tendency in the insula group, but based on an alternative model of the task contingencies (and supported by different regions of the decision-making network). In a probabilistic environment, it is beneficial to select recently reinforced options, and a recent fMRI study indicated that dorsal striatal responses track reinforcement learning parameters in such a task (35). Other work highlights involvement of dorsolateral prefrontal cortex in detecting pattern violations (36) and switching responding after longer runs (37).…”
Section: Discussionmentioning
confidence: 99%